Sliding of Alkylating Anticancer Drugs along the Minor Groove of DNA: New Insights on Sequence Selectivity - Vargiu, Attilio V. (The Biophysical Society, 2008)
Currently, little is known about the molecular recognition pathways between DNA-alkylating anticancer drugs and their targets despite their pharmacological relevance. In the framework of classical molecular dynamics simulations, here we use umbrella sampling to map the potential of mean force (PMF) associated with sliding along the DNA minor groove of two of these compounds. These are an indole derivative of duocarmycin (DSI) and the putative reactive form of anthramycin (anhydro-anthramycin, IMI). Twenty-three configurations were considered for each drug/DNA complex, corresponding to a movement along ∼3 basepairs. The alkylation site turns out to be the most favorable for DSI, while a barrier of ∼6 kcal/mol separates the reactive configuration of IMI·DNA from the absolute minimum. An analysis of various contributions to the PMF reveals that solvent effects play an important role for the largest and more flexible drug DSI. Instead, the PMF of IMI·DNA overall correlates with changes in the binding enthalpy. Implications of these results on the sequence selectivity of the two drugs are discussed.